The metabolism hypothesis of Alzheimer’s disease: from the concept of central insulin resistance and associated consequences to insulin therapy - Morgen, Katrin; Frölich, Lutz (Journal of neural transmission, 2015)
The concept of central insulin resistance and dysfunctional insulin signaling in Alzheimer’s disease (AD) has been developed by Siegfried Hoyer in 1985-2000. It is widely recognized that a cerebrometabolic deficiency is one of the most relevant proximate characteristics of sporadic AD, including functional deficits in oxidative glucose breakdown, oxidative stress and amplifying the action of glucocorticoids in the brain. Insulin and insulin receptors are widely distributed in the brain and are impaired in the post-mortem Alzheimer brain. Functionally, altered insulin signaling may promote synaptic dysfunction and impaired connectivity, especially in highly connected and metabolically active regions of the brain, which in turn predisposes towards AD pathology. Thus, the hypothesis has been proposed that defects in the brain insulin signal transduction system and associated consequences, e.g., oxidative stress, are centrally involved in the etiopathogenesis of sporadic AD. Most importantly, in a research field still awaiting substantial progress in therapeutic options, the idea of AD as a brain type of diabetes mellitus is now being translated into clinical trials with promising early results.
Gesehen am 16.11.2017